2010
DOI: 10.1007/s00247-010-1544-7
|View full text |Cite
|
Sign up to set email alerts
|

Women in pediatric radiology

Abstract: Women represent a significant proportion of pediatric radiologists in the United States, as shown on surveys by the American College of Radiology (ACR) and the Society for Pediatric Radiology (SPR). This review discusses the characteristics of this subgroup of specialists and issues uniquely related to them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…The last author of an article is often the person responsible for the study, and this status may be an indicator of the progression of women into more senior positions in radiology. Interestingly, the percentage of female first authors is consistently greater than the overall percentage of practicing female radiologists, from 19.7% in 1993 to 32.1% in 2013, compared with 14% to 27% of practicing female radiologists from 1995 to 2010 in the United States [5,7], whereas the percentage of senior authors is consistently lower, from 13.6% in 1993 to 19.2% in 2013. Thus, we conclude that there seems to be maintained growth of female academic radiologists, paralleling their presence in the field, in both the participation in and supervision of research.…”
Section: Academic Radiology and Women In Authorship In Radiologymentioning
confidence: 78%
See 4 more Smart Citations
“…The last author of an article is often the person responsible for the study, and this status may be an indicator of the progression of women into more senior positions in radiology. Interestingly, the percentage of female first authors is consistently greater than the overall percentage of practicing female radiologists, from 19.7% in 1993 to 32.1% in 2013, compared with 14% to 27% of practicing female radiologists from 1995 to 2010 in the United States [5,7], whereas the percentage of senior authors is consistently lower, from 13.6% in 1993 to 19.2% in 2013. Thus, we conclude that there seems to be maintained growth of female academic radiologists, paralleling their presence in the field, in both the participation in and supervision of research.…”
Section: Academic Radiology and Women In Authorship In Radiologymentioning
confidence: 78%
“…In contrast, an analysis of female practicing radiologists in 1995 demonstrated that only 14% of all practicing radiologists in the United States were women [5]. Although the overall percentage of practicing female radiologists had grown to 27% in the United States by 2010 [7], it is concerning that the percentage of female residents has remained constant at 27% [6]. If this trend continues, the gender disparity in radiology will not improve in the near future.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations